Prognostic Value of High-Sensitivity Troponin in Acute Coronary Syndromes - Anjuka.R, Anjuka.R; Rao, V.R. Mohan; Hema.M, Hema.M; Vibuja.E, Vibuja.E; Harish, Harish (Journal of Neonatal Surgery, 2025)
Background: Acute coronary syndromes (ACS) represent a spectrum of myocardial ischemia caused by atherosclerotic plaque rupture or coronary occlusion. High-sensitivity cardiac troponin (hs-cTn) assays have revolutionized ACS management by enabling earlier detection of myocardial injury and providing prognostic information. Despite their diagnostic utility, the prognostic implications of hs-cTn in specific ACS subtypes remain incompletely defined. Methods: This prospective cohort study enrolled 90 patients with ACS at a tertiary cardiac center. hs-cTn was measured using a standardized protocol, and patients were stratified by ACS subtype (STEMI, NSTEMI, unstable angina). The primary outcomes included all-cause mortality, recurrent myocardial infarction, and heart failure over 3 months. Multivariable analyses assessed hs-cTn's prognostic value, adjusting for demographic and clinical variables. Results: Patients with STEMI demonstrated the highest median hs-cTn levels (350 ng/L) compared to NSTEMI (120 ng/L) and unstable angina (15 ng/L) (p < 0.001). At 3 months, 15% experienced all-cause mortality, and 28% had major adverse cardiovascular events (MACE). Higher hs-cTn quartiles were associated with increased mortality (24% vs. 5%; HR: 3.8, 95% CI: 2.5–5.8, p < 0.001). Dynamic changes in hs-cTn independently predicted mortality and recurrent events, with an area under the curve (AUC) of 0.87 for mortality in 3 months. Conclusion: Elevated hs-cTn levels at presentation and dynamic changes are significant independent predictors of adverse outcomes in ACS. Integrating hs-cTn into risk models enhances prognostic accuracy and informs therapeutic strategies, particularly in high-risk STEMI and NSTEMI patients. Further studies are needed to refine thresholds for hs-cTn interpretation and evaluate its role in personalized therapy....